Extended Calogero-Bogoyavlenskii-Schiff equation and its dynamical behaviors. (15th November 2021) - Ali, Karmina K; Yilmazer, Resat; Osman, M S
Abstract: In this paper, we consider an extended Calogero-Bogoyavlenskii-Schiff (eCBS) equation. Based on a logarithmic derivative transform and with the aid of symbolic computation, we construct complex multiple solitons for this nonlinear model. Also, by using a symbolic computational method, one-lump solution, two-soliton solution, localized and breather wave solution, as well as a periodic wave solution and multiple wave solutions are obtained. The constraint conditions which ensure the validity of the wave structures are also reported. Besides, the graphs of the solution attained are recorded in 3D graphs by fixing parameters to discuss their dynamical properties. The achieved outcomes show that the applied computational strategy is direct, efficient, concise and can be implemented in more complex phenomena with the assistant of symbolic computations.